Mindfulness-Based Cognitive Therapy—Taking it Further (MBCT-TiF) compared to Ongoing Mindfulness Practice (OMP) in the promotion of well-being and mental health: a randomised controlled trial with graduates of MBCT and MBSR - Maloney, S; Montero-Marin, J; Kuyken, W (Elsevier, 2024)
Objective To evaluate the effectiveness and acceptability of Mindfulness-Based Cognitive Therapy-Taking it Further (MBCT-TiF), as an adapted programme for graduates of MBCT and Mindfulness-Based Stress Reduction (MBSR). MBCT-TiF sits within a global mental health approach, which aims to help shift a wider distribution of the population towards mental well-being and away from mental ill health using a family of MBCT curricula. The primary hypothesis was that MBCT-TiF, compared to Ongoing Mindfulness Practice (OMP), would help MBCT/MBSR graduates improve their mental well-being.